Analysis of Three-Dimensional Morphological Differences in the Mandible between Skeletal Class I and Class II with CBCT Fixed-Point Measurement Method. (7th May 2021) - Dong, Qiang; Shi, HaoYu; Jia, Qi; Tian, Yueyi; Zhi, Keqian; Zhang, Lu
Abstract : This study was aimed at determining the three-dimensional differences in the mandible morphology between skeletal class I and II patients, at exploring the pathogenic mechanisms and morphological characteristics of skeletal class II, and at providing clinical references. The subjects were assigned to two groups according to the size of ANB angle: skeletal class I (2 ° < ANB   angle < 5 ° ) and skeletal class II (5 ° < ANB   angle < 8 ° ). After cone-beam computed tomography (CBCT) scanning, 31 landmarks and 25 measurement items were determined by In Vivo Dental 5.1 software (Anatomage, CA) for statistical analysis. The results were as follows: Co-Go, Go-Me, and CdM-CdD in skeletal class II cases were smaller than those in skeletal class I, and GoR-Me-GoL, GoR-Me-CoL, and, Ig-Men were larger than those in skeletal class I cases. In conclusion, there were significant differences in the three-dimensional morphology of the mandible between skeletal class I and class II patients. The vertical growth of the ramus, the horizontal growth of the mandibular body, and the condyle in skeletal class II patients were smaller than those in skeletal class I cases. In skeletal class II, the growth of the anterior part of the mandible in the vertical direction was larger than that in skeletal class I, and the shape of the mandible was more extended.